2022
DOI: 10.1186/s12920-022-01198-9
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated clinical and osteoclastic phenotypes of Paget’s disease of bone linked to the p.Pro392Leu/SQSTM1 mutation by a rare variant in the DOCK6 gene

Abstract: Background We identified two families with Paget's disease of bone (PDB) linked to the p.Pro392Leu mutation within the SQSTM1 gene displaying a possible digenism. This study aimed at identifying this second genetic variant cosegregating with the p.Pro392Leu mutation and at characterizing its impact on the clinical and cellular phenotypes of PDB. Methods Whole exome sequencing was performed in one patient per family and two healthy controls. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Always remaining in the context of modifying genes, very recently Dessay et al (2022) elegantly identified, by whole exome sequencing in two large unrelated French Canadian PDB families with germline P392L SQSTM1 mutation, a clinically attenuating effect on PDB severity exerted by a V45I rare variant in the DOCK6 gene. Remarkably, albeit both variants were separately found in PDB patients and gave rise to a pagetic phenotype of osteoclasts in vitro versus healthy controls, the DOCK6 variant was found to delay the onset of PDB and attenuate the severity of osteoclast phenotype of PDB caused by the P392L mutation of SQSTM1, when both variants were present.…”
Section: Pfn1 Genementioning
confidence: 99%
See 1 more Smart Citation
“…Always remaining in the context of modifying genes, very recently Dessay et al (2022) elegantly identified, by whole exome sequencing in two large unrelated French Canadian PDB families with germline P392L SQSTM1 mutation, a clinically attenuating effect on PDB severity exerted by a V45I rare variant in the DOCK6 gene. Remarkably, albeit both variants were separately found in PDB patients and gave rise to a pagetic phenotype of osteoclasts in vitro versus healthy controls, the DOCK6 variant was found to delay the onset of PDB and attenuate the severity of osteoclast phenotype of PDB caused by the P392L mutation of SQSTM1, when both variants were present.…”
Section: Pfn1 Genementioning
confidence: 99%
“…DOCK6 protein belongs to the dedicator of cytokinesis (DOCK) family of atypical guanine nucleotide exchange factors, components of intracellular signaling networks and by interacting with small GTPases they probably play a role in actin cytoskeletal reorganization by activating the Rho GTPases Cdc42 and Rac1 (Miyamoto et al, 2007). The same Authors performed a structural bioinformatics analyses showing that the SQSTM1 P392L mutation may decrease its possible intramolecular interaction with the serum response factor-transcription factor (SRF-TF)-like domain, while at the same time the V45I variant of DOCK6 gene may decrease SRF-TF-like activity (Dessay et al, 2022). Indeed, homozygous or dominant negative heterozygous mutations of DOCK6 gene account for the Adams-Oliver syndrome-2, an autosomal recessive multiple congenital anomaly syndrome featured by aplasia cutis congenita and terminal transverse limb defects, in association with variable involvement of the brain, eyes, and cardiovascular system (Shaheen et al, 2011).…”
Section: Pfn1 Genementioning
confidence: 99%